The avian migrant : the biology of bird migration - Rappole, John H. (Columbia University Press, 2013)
The purpose of migration, regardless of the distance involved, is to exploit two or more environments suitable for survival or reproduction over time, usually on a seasonal basis. Yet individual organisms can practice the phenomenon differently, and birds deploy unique patterns of movement over particular segments of time. Incorporating the latest research on bird migration, this concise, critical assessment offers contemporary readers a firm grasp of what defines an avian migrant, how the organism came to be, what is known about its behavior, and how we can resolve its enduring mysteries.